BREED AND ENVIRONMENTAL EFFECTS ON BIRTH WEIGHT, WEANING WEIGHT AND CALVING INTERVAL OF ZEBU CATTLE IN SOUTHEASTERN MEXICO - Jose C. Segura; Juan Gabriel Monforte-Magaña; Jesús R. Aké-López; Victor M. Segura-Correa; José A. Hinojosa-Cuellar; Mario M. Osorio-Arce (Tropical and Subtropical Agroecosystems, 2017)
Records of beef cows from a ranch in southern Mexico gave 1967 birth weights (BW), 1587 weaning weights adjusted to 210 days of age (AWW) and 2001 calving intervals (CI) for the comparison of the breed groups: Brahman (BR), Guzerat (GU), Nellore (NE) and crosses born to zebu dams by Brown Swiss sires. Animals were fed mainly pasture. Data were analysed using general linear procedures. The statistical model that described the data for BW and AWW included the fixed effects of breed group (BR, GU, NE, BS x BR, BS x GU and BS x NE); year of birth or calving (2005 to 2014), season of parity of the cow (dry, rainy, windy), sex of the calf (female or male), parity (1 to =>8) and the simple interaction of year x season of birth or calving. The model for CI was similar to the previous one, except that only the Zebu purebreds were included. The overall means and standard deviations for BW, AWW and CI were 33.5+0.75 kg, 178.9+19.7 kg and 456.4+79.2 days. All effects included in the model had significant effect on BW and AWW, but season and sex on CI. The smallest least squares means for BW corresponded to the cross of BR x NE and the largest to the cross of BS x BR (33.3 and 33.7 kg, respectively); whereas the lowest and largest least squares means for AWW corresponded to the NE (173.8 kg) and BS x BR (191.8 kg). NE cows had shorter CI than BR and GU cows (413.9, 446.2 and 481.3, respectively). Male calves weighed more at birth and weaning than females. Year x season interaction indicate that season effects on performance of calves or cows were not similar throughout the years studied.